IMPACT OF THE LEVEL OF EDUCATION ON THE USES OF MOBILE PHONE: SURVEY OF LITERACY TRAINERS IN NIGER - Idrissa SANDA; Yacouba IDRISSA TIRI; Modibo COULIBALY (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2023)
This research aims to evaluate the impact of the level of the literacy teacher trainers about the use of mobile phone during training sessions at Dogondoutchi (Niger). The analyzed data are from a questionnaire survey of 104 literacy teachertrainers owning personal mobile phones. The analysis of the collected data has revealed a positive correlation between the educational level of the literacy teacher trainers and their level of expertise in mobile phone applications on the one hand, and their use of mobile phones in the training on the second hand. It also appears that these trainers use their mobile phones to interact with colleagues, trainers and resource persons. In addition, as part of their training, these mobile terminals allow them to search for educational resources, store and access them at any time they need them.